2019
DOI: 10.1186/s12879-019-4055-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of chloroquine for treatment of Plasmodium vivax malaria cases in Guragae zone southern Central Ethiopia

Abstract: Background Malaria continues to be a public health problem and important cause of morbidity and mortality in Ethiopia. Due to continuous interventions to combat malaria in endemic regions, a decline in malaria related deaths and morbidity has been registered. These gains, however, are threatened with the emergency of antimalarial drugs resistant strains of plasmodium parasites. This study aimed to determine therapeutic efficacy of chloroquine for treatment of Plasmodium vivax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
5
14
0
Order By: Relevance
“…In addition, the performance difference of the laboratory personnel regarding malaria species identification might be attributed to increased prevalence. However, despite emerging chloroquine resistance P. vivax has been reported in southern Ethiopia [10], chloroquine is an efficacious drug for the treatment of P. vivax malaria in the study area [23].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, the performance difference of the laboratory personnel regarding malaria species identification might be attributed to increased prevalence. However, despite emerging chloroquine resistance P. vivax has been reported in southern Ethiopia [10], chloroquine is an efficacious drug for the treatment of P. vivax malaria in the study area [23].…”
Section: Discussionmentioning
confidence: 91%
“…In general, the prevalence of malaria in Wolkite health center showed a consistent downward trend from the year of 2015-2018. Plasmodium vivax seemed to be overlooked even though there were hardly any known drug resistance has been reported in the study area for P. vivax [23]. In addition, a recent randomized trial has reported the effectiveness and safety of short-course usage of Primaquine for a radical cure in P. vivax endemic areas of Ethiopia [34].…”
Section: Resultsmentioning
confidence: 96%
“…Five studies reported data from a single study site (Bishoftu/Debrezeit) in different years and seasons [ 20 , 23 , 26 28 ]. Two other studies reported data from another single study site (Adama/Naziret) [ 26 , 27 ]. Figure 2 shows the distribution of the study sites from where the efficacy status of CQ has been reported (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies from Ethiopia have reported a decreasing sensitivity of P. vivax to CQ [ 22 – 24 ], although this appears sporadic as some studies showed sustained efficacy of this drug [ 25 – 27 ]. Although not officially recommended in the Ethiopian malaria treatment guidelines, studies have investigated the efficacy of alternative treatments for vivax malaria, such as treatment with artemether-lumefantrine (AL); CQ combined with PQ; or, AL with PQ [ 25 , 28 – 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The malaria incidence rate in 2015 was 91 per 1000 people at risk with an estimate of 214 million of new cases and 438000 mortalities [7]. The co-infection of HIV and Malaria are a burden, especially East and central African countries [26][27][28][29], in Ethiopia, mortalities from Malaria is current too high in either among citizens or migrants [8,30], and similar for tuberculosis [31,32].…”
Section: Introductionmentioning
confidence: 99%